Studi Literatur: Efektivitas Metode Pembelajaran Quantum Learning Terhadap Hasil Belajar Siswa - Anggi Dwi Noperlis; Neviyarni (eductum: Jurnal Literasi Pendidikan, 2022)
In determining an effective learning method as a teacher must be able to choose what method to use, Quantum Learning is one of the learning methods. The concept of the Quantum Learning Mode creates fun learning so as to create a happy atmosphere. In this study, the aim was to find out the abilities of students who received Quantum Learning learning mode. The method used is by analyzing the literature review, in this case, the researcher analyzed previous studies. The results of the study found that the Quantum Learning mode was effective in improving student learning outcomes.